2023
DOI: 10.3389/fnmol.2023.1118746
|View full text |Cite
|
Sign up to set email alerts
|

Layer-specific changes of KCC2 and NKCC1 in the mouse dentate gyrus after entorhinal denervation

Abstract: The cation-chloride cotransporters KCC2 and NKCC1 regulate the intracellular Cl− concentration and cell volume of neurons and/or glia. The Cl− extruder KCC2 is expressed at higher levels than the Cl− transporter NKCC1 in mature compared to immature neurons, accounting for the developmental shift from high to low Cl− concentration and from depolarizing to hyperpolarizing currents through GABA-A receptors. Previous studies have shown that KCC2 expression is downregulated following central nervous system injury, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…For example, in a pharmacological model of cognitive impairment associated with schizophrenia, NKCC1 is increased in the ventral but not in the dorsal subregion of the medial prefrontal cortex (mPFC) [51], and in a rodent model of neuropathic pain, KCC2 expression is increased in the mPFC but not in the neighboring anterior cingulate cortex [16]. NKCC1 and KCC2 can also be differentially regulated in different layers within the same brain areas, as shown in mouse granule cells and outer and middle molecular layers following entorhinal denervation [52].…”
Section: Cell Type and Spatial Heterogeneity Of Chloride Transportersmentioning
confidence: 99%
“…For example, in a pharmacological model of cognitive impairment associated with schizophrenia, NKCC1 is increased in the ventral but not in the dorsal subregion of the medial prefrontal cortex (mPFC) [51], and in a rodent model of neuropathic pain, KCC2 expression is increased in the mPFC but not in the neighboring anterior cingulate cortex [16]. NKCC1 and KCC2 can also be differentially regulated in different layers within the same brain areas, as shown in mouse granule cells and outer and middle molecular layers following entorhinal denervation [52].…”
Section: Cell Type and Spatial Heterogeneity Of Chloride Transportersmentioning
confidence: 99%
“…As hippocampal neurons receive a highly layer-specific input, differences in pathway activity could result in differences in spine head sizes and their distributions in each layer. Along this line, layer-specific stimulation of granule cells, such as high-frequency stimulation of the perforant path (Jungenitz et al 2014(Jungenitz et al , 2018 or layer-specific denervation of granule cells (del Turco et al 2023;Deller and Frotscher 1997;Deller et al 2007;Vuksic et al 2011), could theoretically shift the spine head size distribution away from lognormality-or change its skewness or mean. Indeed, alterations in the mean and skewness of spine size distributions have been detected following layer-specific stimulation of perforant path synapses in vivo (Rößler et al 2023), but without a loss of lognormality.…”
Section: Functional Alterations Do Not Degrade the Lognormal Distribu...mentioning
confidence: 99%
“…Nevertheless, spatially resolved studies have investigated the changes in KCC2 and NKCC1 induced by lesions, providing a clear understanding of whether precise, anatomically well-defined lesions can elicit spatially restricted, layer-specific alterations in the expression of these proteins. Turco et al recently demonstrated that entorhinal denervation induces specific changes in the expression of KCC2 and NKCC1 in the molecular layers of the dentate gyrus, specifically the oml/mml layers [ 69 ]. Through the use of laser microdissection, microarray analysis, and RT-qPCR, they identified a decrease in KCC2 mRNA and reduced levels of KCC2 protein in denervated granule cell dendrites.…”
Section: The Role Of Kcc2 In Epileptogenesismentioning
confidence: 99%